Diseño conceptual de una turbina eólica espiral de arquímedes con potencia mecánica máxima de 1 kw. - Castro Niza, Alan Michael (2022)
In this research project, the knowledge acquired during training in various fields of electromechanical engineering was applied to model and simulate the operation of an Archimedean spiral wind turbine, which has been subjected to meteorological phenomena that exist in the urban area. of the Latacunga canton. With the use of the meteorological station it was possible to calculate the average speed of 3.89 m/s and the maximum measured speed of 9.6 m/s, in the area the wind occurs in greater quantity from the south-east. After the analysis of the wind potential, it is deduced that it was not possible to generate 1 kW of mechanical energy because in the place of data collection, the wind speed is not enough to reach said power, another option was to increase the diameter of the rotor , but this is not viable because the project is focused on the urban area, through the calculations of power generation the design parameters were specified that allow to take full advantage of the kinetic energy of the wind, the diameter of the rotor is 1, 5 m with a length of 1.18 m and an angle of attack of 45º. These measurements make it possible to generate a power of 33.25 W with the average speed and 485.73 W with the maximum speed measured. To reach the maximum power of 1 kW under the same design parameters, a wind speed equal to or greater than 15 m/s is necessary.